Effects of acute systemic administration of cannabidiol on sleep-wake cycle in rats. (March 2013) - Chagas, Marcos Hortes N; Crippa, José Alexandre S; Zuardi, Antonio Waldo; Hallak, Jaime E C; Machado-de-Sousa, João Paulo; Hirotsu, Camila; Maia, Lucas; Tufik, Sergio; Andersen, Monica Levy
Cannabidiol (CBD) is one of the main components of Cannabis sativa and has a wide spectrum of action, including effects in the sleep-wake cycle. Objective: The objective of this paper is to assess the effects on sleep of acute systemic administration of CBD. Method: Adult male Wistar rats were randomly distributed into four groups that received intraperitoneal injections of CBD 2.5 mg/kg, CBD 10 mg/kg, CBD 40 mg/kg or vehicle ( n =seven animals/group). Sleep recordings were made during light and dark periods for four days: two days of baseline recording, one day of drug administration (test), and one day after drug (post-test). Results: During the light period of the test day, the total percentage of sleep significantly increased in the groups treated with 10 and 40 mg/kg of CBD compared to placebo. REM sleep latency increased in the group injected with CBD 40 mg/kg and was significantly decreased with the dose of 10 mg/kg on the post-test day. There was an increase in the time of SWS in the group treated with CBD 40 mg/kg, although this result did not reach statistical significance. Conclusion: The systemic acute administration of CBD appears to increase total sleep time, in addition to increasing sleep latency in the light period of the day of administration.